2016
DOI: 10.1007/s10072-016-2743-2
|View full text |Cite
|
Sign up to set email alerts
|

Let’s cut it short: Italian standardization of the MMSPE (Mini-Mental State Pediatric Examination), a brief cognitive screening tool for school-age children

Abstract: A pediatric cognitive screening tool has been shaped in three versions according to school class to assess spatial and temporal orientation, language, reading, writing, drawing, number knowledge, memory, praxis and executive functions in children aged 6-13. It has been standardized on an Italian sample of 807 children. Raw scores were adjusted for critical variables (child's age and parents' education) and a cut-off for the resulting global cognitive score was made available for clinical practice. In line with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Rubial-Alvarez et al [30] found a stronger correlation with chronologic age (r s = 0.8, P< 0.001) and mental age (r s = 0.76, P< 0.001) in healthy children aged between 4 and 12 years, but they did not evaluate boys with DMD [30]. Some authors used a modified MMSE version, instead of the original one for healthy children, and therefore their results should not be compared with our data [27,28,31,32].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Rubial-Alvarez et al [30] found a stronger correlation with chronologic age (r s = 0.8, P< 0.001) and mental age (r s = 0.76, P< 0.001) in healthy children aged between 4 and 12 years, but they did not evaluate boys with DMD [30]. Some authors used a modified MMSE version, instead of the original one for healthy children, and therefore their results should not be compared with our data [27,28,31,32].…”
Section: Discussionmentioning
confidence: 67%
“…The Brazilian researchers evaluated 103 children (6 to 9 years) with learning disabilities. The Italian study has been shaped MMSE in three different versions according to school class in children aged 6 to 13 [31,32]. Original MMSE or modified versions of MMSE has not been explored in other specific neurological diseases in childhood.…”
mentioning
confidence: 99%
“…MMC can be applied in the age group from 3 to 14 years old. The MMC application lasts from 5 to 7 min and has been used in several countries, including Brazil (Viegas et al 2021 ; Jain and Passi 2005 ; Moura et al 2017 ; Shoji et al 2002 ; Rubial-Álvarez et al 2007 ; Scarpa et al 2017 ; Peviani et al 2020 ). Cognitive function was assessed according to the total score.…”
Section: Methodsmentioning
confidence: 99%
“…MMC can be applied to individuals from 3 to 14 years old. MMC application lasts from five to seven minutes and has been used in several countries, including Brazil (Shoji et al, 2002;Jain & Passi, 2005;Rubial-Alvarez et al, 2007;Moura et al, 2017;Scarpa et al, 2017;Peviani et al, 2020;Viegas et al, 2021). The evaluation of each child was performed in a reserved room within the school.…”
Section: Instrumentsmentioning
confidence: 99%